Two “Colored” Women’s Conversation About the Relevance of Feminist Law Journals in the Twenty-First Century - Banks, Taunya Lovell; Andrews, Penelope (Columbia Journal of Gender and Law, 2003)
The invitation to participate in the Columbia Journal of Gender and Law symposium on the relevance of feminist law journals provided an ideal opportunity for us to reassess our collective endeavors as teachers, scholars, and advocates committed to social justice. Feminist methodology and epistemology have been instrumental in shaping our conceptual frameworks. So, too, have other theories of law that seek to unearth the structural impediments, hidden biases, and methodological limitations of the law in redressing injustice. As black women (one from the United States and the other from South Africa), the concerns of race have been central to our analysis of the world and in our decisions to be lawyers. It is through the prism of racial discrimination that we confronted injustice, and our early endeavors, both academic and practical, used law as an instrument to eliminate injustice. Feminism came into our lives later, but it served to enrich our analysis about overcoming all impediments to equality. This was particularly important as the focus of equality both in the United States and South Africa served to privilege racial equality while ignoring the intersection of race and gender on the status of women. Feminist law journals have been an indispensable part of our intellectual journeys-one that we plan to continue on as the nature and forms of discrimination alter. We embarked on the conversation that follows in an attempt to assess the influence of feminist law journals on our lives and scholarship, and where we would like to see feminist law journals go in the future.